2022
DOI: 10.3389/fpls.2022.966789
|View full text |Cite
|
Sign up to set email alerts
|

Delaying ripening using 1-MCP reveals chilling injury symptom development at the putative chilling threshold temperature for mature green banana

Abstract: Storage at the putative chilling threshold temperature (CTT) to avoid chilling injury still limits postharvest handling of tropical fruit like banana in that ripening may occur at the CTT. To determine whether chilling injury (CI) symptoms would develop in mature green (MG) banana fruit if the CTT exposure was extended by inhibiting ethylene action and thus ripening, 1-methylcyclopropene (1-MCP) was applied. Individual ‘fingers’ from multiple ‘clusters’ of MG bananas were either immersed in water or 50 μg L−1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 57 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…To mitigate these effects, 1-MCP treatment has been shown to effectively maintain the sensory and physiological quality of fruit during storage while reducing the incidence of CI. Cheng et al [27] showed that 1-MCP could reduce the occurrence of CI in jujube fruit and increase the activity of key enzymes in the antioxidant system; it has also been verified in fruit such as green banana [28], kiwifruit [29], sweet persimmon [30], pomegranate [31], apple [32], and peach [33]. In this study, low-temperature stress effects were observed in 'Xiangjiao' plums stored at 4 • C at 15 d in the control group (CK).…”
Section: Discussionmentioning
confidence: 92%
“…To mitigate these effects, 1-MCP treatment has been shown to effectively maintain the sensory and physiological quality of fruit during storage while reducing the incidence of CI. Cheng et al [27] showed that 1-MCP could reduce the occurrence of CI in jujube fruit and increase the activity of key enzymes in the antioxidant system; it has also been verified in fruit such as green banana [28], kiwifruit [29], sweet persimmon [30], pomegranate [31], apple [32], and peach [33]. In this study, low-temperature stress effects were observed in 'Xiangjiao' plums stored at 4 • C at 15 d in the control group (CK).…”
Section: Discussionmentioning
confidence: 92%
“…Malondialdehyde (MDA) content was assessed by the thiobarbituric acid (TBA) test . Approximately 0.1 g fresh roots, stems and leaves were homogenized in 5 mL of 100 g L –1 trichloroacetic acid and centrifuged at 10, 000 g for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Malondialdehyde (MDA) content was assessed by the thiobarbituric acid (TBA) test. 32 Approximately 0.1 g fresh roots, stems and leaves were homogenized in 5 mL of 100 g L −1 trichloroacetic acid and centrifuged at 10, 000g for 10 min. The supernatant was mixed with 5 mL 0.5% barbituric acid (TBA; prepared with 20% TCA) and heated in boiling water for 15 min.…”
Section: Atomic Force Microscope (Afm)mentioning
confidence: 99%
“…This stress leads to the production of reactive oxygen species (ROS) and the degradation of the cell membrane. Consequently, these changes initiate a chain reaction of lipid oxidation, leading to oxidative damage and membrane dysfunction in cells [49,50]. MT is an endogenous indole molecule with numerous biological functions in plants, particularly inducing stress tolerance [41].…”
Section: CI Membrane Permeability and Mda Levelsmentioning
confidence: 99%